Transparent conductive film material and preparation method thereof
Through the combination of three-layer coextrusion technology and specific materials, transparent conductive film materials with high conductivity and good transparency were prepared, which solved the problems of electrostatic accumulation and anti-static properties of traditional plastic films, and achieved efficient electrostatic conduction and long life of the film material.
Patent Information
- Application Number
- CN202510315814.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-18
AI Technical Summary
Due to the insulating properties of traditional plastic films, they are prone to accumulate static charges during production, transportation and storage, and cannot meet the antistatic needs. The commonly used antistatic layer coating method can easily lead to short coating life, reduced antistatic performance or reduced transparency.
A transparent conductive film material is prepared by three-layer co-extrusion technology. The outer layer contains iron hybrid multi-wall carbon nanotubes as the conductive enhancer, and the inner layer uses aluminum-doped zinc oxide and indium tin oxide as the composite conductive material. By controlling the mass ratio of the material and the treatment method, the conductivity and transparency of the film material are improved.
It achieves high conductivity and good transparency of the film material, can effectively export static electricity, is suitable for packaging materials with high antistatic demand, and at the same time extends the service life of the film material.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of plastic film manufacturing, and more specifically, to a transparent conductive film material and a preparation method thereof. Background Art
[0002] With the rapid development of microelectronic products and other precision industrial products, the demand for packaging materials with antistatic properties is growing. Due to its insulating properties, traditional plastic films are prone to accumulate a large amount of static charge during production, transportation and storage, which may damage the products packaged inside. It cannot meet the needs of product packaging that requires antistatic properties, such as solvent-based glue.
[0003] With the development of science and technology, the market demand for high-performance film materials with both transparency and conductivity is growing. Antistatic coating or blending is often used to improve its conductivity. However, the coating life is short, the antistatic performance is reduced, or the transparency of the film is reduced, which affects the appearance and use of the plastic film. The conductivity and transparency of the film cannot be taken into account at the same time. Summary of the invention
[0004] In order to improve the conductivity and transparency of a film material, the present application provides a transparent conductive film material and a preparation method thereof.
[0005] In a first aspect, the present application provides a transparent conductive film material, which adopts the following technical solution: A transparent conductive film material comprises two outer layers and an inner layer, wherein the outer layer comprises the following raw materials in parts by weight: 50-65 parts of high-density polyethylene powder and 2.5-4.8 parts of a conductive enhancer; the conductive enhancer is iron-hybridized multi-walled carbon nanotubes; and the inner layer comprises the following raw materials in parts by weight: polyester particles and a composite conductive material, wherein the addition amount of the composite conductive material is 5-8wt% of the polyester particles, and the composite conductive material comprises aluminum-doped zinc oxide and indium tin oxide.
[0006] By adopting the above technical scheme, both polyester and high-density polyethylene have good transparency, and a conductive enhancer is added to the outer layer. The iron-hybridized multi-walled carbon nanotubes have good conductivity, so that when the amount of the conductive enhancer added is small, the resistance of the outer layer can be reduced, and the generated static electricity can be discharged without affecting the transparency of the outer layer of the film. Aluminum-doped zinc oxide and indium tin oxide have good transparency and conductivity. Aluminum-doped zinc oxide and indium tin oxide cooperate with each other to effectively improve the conductivity of the inner layer of the film without affecting the transparency of the inner layer of the film.
[0007] Preferably, in the composite conductive material, the mass ratio of aluminum-doped zinc oxide to indium tin oxide is (1.62-1.75):(1.21-1.34).
[0008] By adopting the above technical solution and controlling the mass ratio of aluminum-doped zinc oxide and indium tin oxide, the composite conductive material formed by the two can have better conductivity and exert a synergistic effect, thereby further improving the conductivity of the film material.
[0009] Preferably, the preparation method of the iron-hybridized multi-walled carbon nanotubes comprises the following steps: ultrasonically dispersing multi-walled carbon nanotubes, ferric chloride and ferrous sulfate heptahydrate in water, introducing nitrogen and mixing for 2 hours, adding ammonia water dropwise, and after the addition is complete, placing the mixed solution in an oven at 60°C for 3 hours, precipitating, centrifuging, and washing to obtain iron-hybridized multi-walled carbon nanotubes.
[0010] By adopting the above technical solution, the multi-walled carbon nanotubes are hybridized with ferroferric oxide, which further improves the conductivity of the iron-hybridized multi-walled carbon nanotubes and reduces their resistance, thereby improving the conductivity of the outer layer of the film material.
[0011] Preferably, the mass ratio of the ferric chloride, ferrous sulfate heptahydrate and multi-walled carbon nanotubes is (1.32-1.68):(0.67-0.73):(0.11-0.15).
[0012] By adopting the above technical scheme, the mass ratio of ferric chloride, ferrous sulfate heptahydrate and multi-walled carbon nanotubes is controlled, so that the ferrosoferric oxide generated by the reaction can be better combined with the multi-walled carbon nanotubes, thereby increasing the iron loading in the iron-hybridized multi-walled carbon nanotubes and ensuring the conductivity of the iron-hybridized multi-walled carbon nanotubes.
[0013] Preferably, the iron-hybridized multi-walled carbon nanotubes are further subjected to a silica coating treatment: the iron-hybridized multi-walled carbon nanotubes are mixed with anhydrous ethanol and water, and after being uniformly dispersed by ultrasonication, an ethanol solution of tetraethyl orthosilicate is added dropwise, and the reaction is carried out for 24 hours after the addition is completed, an ethanol solution of a silane coupling agent is added dropwise, and the reaction is continued for 24 hours, and then the mixture is filtered, washed, and vacuum dried.
[0014] By adopting the above technical scheme, tetraethyl orthosilicate is hydrolyzed to generate silicon dioxide, which is deposited and attached to the surface of iron-hybridized multi-walled carbon nanotubes and modified by a silane coupling agent, so that the iron-hybridized multi-walled carbon nanotubes have good dispersibility and can improve the mechanical properties of the film material.
[0015] Preferably, the iron-hybridized multi-walled carbon nanotubes after the silica coating treatment are further subjected to the following treatment: ultrasonically dispersing the iron-hybridized multi-walled carbon nanotubes after the silica coating treatment in a pyrrole hydrochloric acid solution, stirring in an ice-water bath for 30 minutes, adding ferric chloride solution dropwise, stirring at 0-5°C for 2.5 hours, filtering and drying.
[0016] By adopting the above technical solution, pyrrole can self-polymerize and form a polypyrrole layer on the surface of the iron-hybridized multi-walled carbon nanotubes after silica coating. Polypyrrole has good conductivity and can further improve the conductivity of the iron-hybridized multi-walled carbon nanotubes after silica coating.
[0017] Preferably, the mass ratio of the iron-hybridized multi-walled carbon nanotubes after the silica coating treatment to pyrrole is (1.68-1.75):(0.92-1.03).
[0018] By adopting the above technical solution, the mass ratio of the iron hybrid multi-walled carbon nanotubes coated with silica to pyrrole is controlled, so that the polypyrrole covers the iron hybrid multi-walled carbon nanotubes coated with silica completely and evenly, which is beneficial to improving the conductivity of the conductivity enhancer.
[0019] In a second aspect, the present application provides a method for preparing a transparent conductive film material, which adopts the following technical solution: A method for preparing a transparent conductive film material comprises the following steps: mixing high-density polyethylene powder with a conductive enhancer to prepare an outer layer raw material for standby use; mixing polyester particles, aluminum-doped zinc oxide and indium tin oxide to prepare an inner layer raw material for standby use; and co-extruding the outer layer raw material and the inner layer raw material in an outer layer-inner layer-outer layer arrangement to prepare the transparent conductive film material.
[0020] By adopting the above technical solution, the prepared transparent conductive film material has excellent conductivity and transparency, and is suitable for packaging with high antistatic requirements.
[0021] In summary, this application has the following beneficial effects: 1. Since the polyester and high-density polyethylene in this application have good transparency, a conductive enhancer is added to the outer layer, and the iron-hybridized multi-walled carbon nanotubes have good conductivity, a small amount of addition can reduce the resistance of the outer layer and conduct the generated static electricity without affecting the transparency of the outer layer of the film. Aluminum-doped zinc oxide and indium tin oxide have good transparency and conductivity. Aluminum-doped zinc oxide and indium tin oxide cooperate with each other to effectively improve the conductivity of the inner layer of the film without affecting the transparency of the inner layer of the film.
[0022] 2. In the present application, the mass ratio of aluminum-doped zinc oxide and indium tin oxide is controlled so that the composite conductive material formed by the two can have better conductivity and exert a synergistic effect, thereby further improving the conductivity of the film material.
[0023] 3. In the present application, ferroferric oxide is used to hybridize the multi-walled carbon nanotubes, which further improves the conductivity of the iron-hybridized multi-walled carbon nanotubes and reduces their resistance, thereby improving the conductivity of the outer layer of the film material. DETAILED DESCRIPTION
[0024] The present application is further described in detail below with reference to the embodiments.
[0025] Conductive Enhancer Preparation Example 1-10
[0026] Preparation Example 1 The preparation method of iron-hybridized multi-walled carbon nanotubes comprises the following steps: ultrasonically dispersing 0.13 g of multi-walled carbon nanotubes, ferric chloride and ferrous sulfate heptahydrate in water, wherein the mass ratio of ferric chloride, ferrous sulfate heptahydrate and multi-walled carbon nanotubes is 1.32:0.67:0.11; introducing nitrogen and mixing for 2 hours; dripping 5 mL of ammonia water; after the dripping is completed, placing the mixed solution in an oven at 60° C. for 3 hours, precipitating, centrifuging and washing to obtain the iron-hybridized multi-walled carbon nanotubes.
[0027] Preparation Example 2 The preparation method of iron-hybridized multi-walled carbon nanotubes comprises the following steps: ultrasonically dispersing 0.15 g of multi-walled carbon nanotubes, ferric chloride and ferrous sulfate heptahydrate in water, wherein the mass ratio of ferric chloride, ferrous sulfate heptahydrate and multi-walled carbon nanotubes is 1.68:0.73:0.15; introducing nitrogen and mixing for 2 hours; dripping 5 mL of ammonia water; after the dripping is completed, placing the mixed solution in an oven at 60° C. for 3 hours, precipitating, centrifuging and washing to obtain the iron-hybridized multi-walled carbon nanotubes.
[0028] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that the mass ratio of ferric chloride, ferrous sulfate heptahydrate and multi-walled carbon nanotubes is 1.32:1.56:0.05.
[0029] Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that the mass ratio of ferric chloride, ferrous sulfate heptahydrate and multi-walled carbon nanotubes is 1.32:0.21:0.35.
[0030] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 1 is that the iron-hybridized multi-walled carbon nanotubes are also coated with silica: 1.58g of iron-hybridized multi-walled carbon nanotubes are mixed with 80mL of anhydrous ethanol and 80mL of water, and after ultrasonic dispersion, 16mL of 15wt% ethanol solution of tetraethyl orthosilicate is added dropwise, and the reaction is carried out for 24h after the addition is completed. 12mL of 12wt% ethanol solution of silane coupling agent KH-570 is added dropwise, and the reaction is continued for 24h, filtered, washed, and vacuum dried.
[0031] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 1 is that the iron-hybridized multi-walled carbon nanotubes are also coated with silica: 1.35g of iron-hybridized multi-walled carbon nanotubes are mixed with 75mL of anhydrous ethanol and 70mL of water, and after ultrasonic dispersion, 20mL of 15wt% ethanol solution of tetraethyl orthosilicate is added dropwise, and the reaction is carried out for 24h after the addition is completed. 15mL of 12wt% ethanol solution of silane coupling agent KH-570 is added dropwise, and the reaction is continued for 24h, filtered, washed, and vacuum dried.
[0032] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 5 is that the iron hybridized multi-walled carbon nanotubes after silica coating are further subjected to the following treatment: the iron hybridized multi-walled carbon nanotubes after silica coating are ultrasonically dispersed in a 45wt% pyrrole hydrochloric acid solution, the mass ratio of the iron hybridized multi-walled carbon nanotubes after silica coating to pyrrole is 1.68:0.92, after stirring in an ice-water bath for 30 minutes, 0.1 mol / L ferric chloride solution is added dropwise, stirred at 5°C for 2.5 hours, filtered and dried.
[0033] Preparation Example 8 The difference between Preparation Example 8 and Preparation Example 5 is that the iron hybridized multi-walled carbon nanotubes after silica coating are further subjected to the following treatment: the iron hybridized multi-walled carbon nanotubes after silica coating are ultrasonically dispersed in a 45wt% pyrrole hydrochloric acid solution, the mass ratio of the iron hybridized multi-walled carbon nanotubes after silica coating to pyrrole is 1.75:1.03, after stirring in an ice-water bath for 30 minutes, 0.1 mol / L ferric chloride solution is added dropwise, stirred at 0°C for 2.5 hours, filtered and dried.
[0034] Preparation Example 9 The difference between Preparation Example 9 and Preparation Example 7 is that the mass ratio of the iron hybridized multi-walled carbon nanotubes to pyrrole after the silica coating treatment is 1.68:0.25.
[0035] Preparation Example 10 The difference between Preparation Example 10 and Preparation Example 7 is that the mass ratio of the iron hybridized multi-walled carbon nanotubes to pyrrole after the silica coating treatment is 1.68:1.85.
[0036] Example 1 A transparent conductive film material comprises two outer layers and an inner layer, wherein the outer layer comprises the following raw materials in parts by weight: 50 kg of high-density polyethylene powder and 2.5 kg of a conductive enhancer, wherein the high-density polyethylene powder is HDPE6070, and the conductive enhancer is the conductive enhancer prepared in Preparation Example 1; the inner layer comprises the following raw materials in parts by weight: polyester particles and a composite conductive material, wherein the polyester particles are PET-1120, and the addition amount of the composite conductive material is 5 wt % of the polyester particles, and the composite conductive material comprises aluminum-doped zinc oxide and indium tin oxide, and the mass ratio of the aluminum-doped zinc oxide to the indium tin oxide is 1.62:1.21.
[0037] The preparation method of the above-mentioned transparent conductive film material includes the following steps: mixing high-density polyethylene powder with a conductive enhancer to prepare an outer layer raw material for use; mixing polyester particles, aluminum-doped zinc oxide and indium tin oxide to prepare an inner layer raw material for use; and co-extruding the outer layer raw material and the inner layer raw material in three layers in the arrangement of outer layer-inner layer-outer layer to prepare a transparent conductive film material.
[0038] Example 2 A transparent conductive film material comprises two outer layers and an inner layer, wherein the outer layer comprises the following raw materials in parts by weight: 65 kg of high-density polyethylene powder and 4.8 kg of a conductive enhancer, wherein the high-density polyethylene powder is HDPE6070, and the conductive enhancer is the conductive enhancer prepared in Preparation Example 2; the inner layer comprises the following raw materials in parts by weight: polyester particles and a composite conductive material, wherein the polyester particles are PET-1120, and the addition amount of the composite conductive material is 8 wt % of the polyester particles, and the composite conductive material comprises aluminum-doped zinc oxide and indium tin oxide, and the mass ratio of the aluminum-doped zinc oxide to the indium tin oxide is 1.75:1.34.
[0039] The preparation method of the above-mentioned transparent conductive film material includes the following steps: mixing high-density polyethylene powder with a conductive enhancer to prepare an outer layer raw material for use; mixing polyester particles, aluminum-doped zinc oxide and indium tin oxide to prepare an inner layer raw material for use; and co-extruding the outer layer raw material and the inner layer raw material in three layers in the arrangement of outer layer-inner layer-outer layer to prepare a transparent conductive film material.
[0040] Example 3 The difference between Example 3 and Example 1 is that the conductivity enhancer is the conductivity enhancer prepared in Preparation Example 3.
[0041] Example 4 The difference between Example 4 and Example 1 is that the conductivity enhancer is the conductivity enhancer prepared in Preparation Example 4.
[0042] Example 5 The difference between Example 5 and Example 1 is that the conductivity enhancer is the conductivity enhancer prepared in Preparation Example 5.
[0043] Example 6 The difference between Example 6 and Example 1 is that the conductivity enhancer is the conductivity enhancer prepared in Preparation Example 6.
[0044] Example 7 The difference between Example 7 and Example 1 is that the conductivity enhancer is the conductivity enhancer prepared in Preparation Example 7.
[0045] Example 8 The difference between Example 8 and Example 1 is that the conductivity enhancer is the conductivity enhancer prepared in Preparation Example 8.
[0046] Example 9 The difference between Example 9 and Example 1 is that the conductivity enhancer is the conductivity enhancer prepared in Preparation Example 9.
[0047] Example 10 The difference between Example 10 and Example 1 is that the conductivity enhancer is the conductivity enhancer prepared in Preparation Example 10.
[0048] Embodiment 11 The difference between Example 11 and Example 1 is that in the composite conductive material, the mass ratio of aluminum-doped zinc oxide to indium tin oxide is 1.62:0.25.
[0049] Example 12 The difference between Example 12 and Example 1 is that in the composite conductive material, the mass ratio of aluminum-doped zinc oxide to indium tin oxide is 1.62:1.98.
[0050] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the added amount of the composite conductive material is 2 wt % of the polyester particles.
[0051] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the added amount of the composite conductive material is 12 wt % of the polyester particles.
[0052] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that no conductive enhancer is added to the outer layer.
[0053] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that an equal amount of aluminum-doped zinc oxide is used instead of the composite conductive material.
[0054] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that an equal amount of indium tin oxide is used instead of the composite conductive material.
[0055] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that no composite conductive material is added to the inner layer.
[0056] According to the raw materials and preparation methods of Examples 1-12 and Comparative Examples 1-6, transparent conductive films were prepared. The resistance of the films was tested using a resistivity tester, and the haze of the films was tested using a haze meter. The results are recorded in Table 1.
[0057] Table 1 Resistance and haze of film materials project Resistance / Ω Haze / % Example 1 <![CDATA[1.25×10 8 ]]> 1.68 Example 2 <![CDATA[1.23×10 8 ]]> 1.67 Example 3 <![CDATA[2.22×10 8 ]]> 1.69 Example 4 <![CDATA[2.23×10 8 ]]> 1.68 Example 5 <![CDATA[1.02×10 8 ]]> 1.12 Example 6 <![CDATA[1.06×10 8 ]]> 1.05 Example 7 <![CDATA[1.04×10 8 ]]> 1.67 Example 8 <![CDATA[1.03×10 8 ]]> 1.68 Example 9 <![CDATA[1.98×10 8 ]]> 1.67 Example 10 <![CDATA[2.01×10 8 ]]> 1.68 Embodiment 11 <![CDATA[2.13×10 8 ]]> 1.69 Example 12 <![CDATA[2.15×10 8 ]]> 1.76 Comparative Example 1 <![CDATA[2.95×10 9 ]]> 1.69 Comparative Example 2 <![CDATA[2.86×10 9 ]]> 1.56 Comparative Example 3 <![CDATA[1.25×10 10 ]]> 1.67 Comparative Example 4 <![CDATA[3.58×10 8 ]]> 1.69 Comparative Example 5 <![CDATA[3.67×10 8 ]]> 1.69 Comparative Example 6 <![CDATA[1.59×10 10 ]]> 1.68 According to Examples 1-2, Comparative Example 3, Comparative Example 6, and Table 1, it can be seen that the film material prepared in Examples 1-2 has lower resistance and lower haze, indicating that the film material prepared in Examples 1-2 has good conductivity and transparency. Both polyester and high-density polyethylene have high transparency, but good insulation. A conductive enhancer is added to the outer layer. The iron-hybridized multi-walled carbon nanotubes have good conductivity, so that a small amount of the conductive enhancer can reduce the resistance of the outer layer and conduct the generated static electricity. At the same time, due to the small amount of the conductive enhancer, the transparency of the outer layer of the film is not affected. A composite conductive material is added to the inner layer. Both aluminum-doped zinc oxide and indium tin oxide have good conductivity, and their cooperation can effectively improve the conductivity of the inner layer of the film. In addition, aluminum-doped zinc oxide and indium tin oxide have good transparency and do not affect the transparency of the inner layer of the film.
[0058] Compared with Example 1-2, the resistance of the film material prepared in Example 3-4 increases and the conductivity decreases. During the preparation of the conductivity enhancer used in Example 3-4, the mass ratio of ferric chloride, ferrous sulfate heptahydrate and multi-walled carbon nanotubes was changed, which directly affected the deposition of ferrosoferric oxide on the surface of the multi-walled carbon nanotubes and the degree of bonding between ferrosoferric oxide and the multi-walled carbon nanotubes. After the mass ratio was changed, the deposition amount of ferrosoferric oxide decreased or the degree of bonding with the multi-walled carbon nanotubes decreased, thereby reducing the conductivity of the iron-hybridized multi-walled carbon nanotubes, and further reducing the conductivity of the film material.
[0059] Compared with Example 1-2, the resistance and haze of the film material prepared in Example 5-6 are reduced, and the conductivity and transparency are improved. When preparing the conductive enhancer used in Example 5-6, the iron-hybridized multi-walled carbon nanotubes are treated with silicon dioxide and a silane coupling agent. Tetraethyl orthosilicate is hydrolyzed to generate silicon dioxide, which is deposited and attached to the surface of the iron-hybridized multi-walled carbon nanotubes and modified with a silane coupling agent. This makes the iron-hybridized multi-walled carbon nanotubes have good dispersibility and can improve the mechanical properties of the film material.
[0060] Compared with Example 5-6, the resistance of the film material prepared in Example 5-6 is reduced and the conductivity is improved. The conductivity enhancer used in Example 7-8 is subjected to pyrrole coating treatment during preparation. Pyrrole self-polymerizes on the surface of the iron-hybridized multi-walled carbon nanotubes after the silica coating treatment to form a polypyrrole layer. Polypyrrole has good conductivity. The coated conductivity enhancer has better conductivity, thereby improving the conductivity of the film material.
[0061] Compared with Examples 7-8, the resistance of the film material prepared in Examples 9-10 increased and the conductivity decreased. During the preparation of the conductive enhancer used in Examples 7-8, the mass ratio of the iron-hybridized multi-walled carbon nanotubes after the silica coating treatment to pyrrole was changed. When the mass ratio decreased, the polypyrrole layer did not fully coat the iron-hybridized multi-walled carbon nanotubes after the silica coating treatment, thereby reducing the loading amount of the polypyrrole. When the mass ratio increased, the pyrrole self-polymerized and agglomerated, and the morphology of the polypyrrole layer was poor, thereby affecting the conductive properties of the conductive enhancer.
[0062] Compared with Examples 1-2, Examples 11-12 and Comparative Examples 4-5 show that the resistance of the film material prepared in Examples 11-12 increases and the conductivity decreases. Examples 11-12 change the mass ratio of aluminum-doped zinc oxide and indium tin oxide. In Comparative Example 4, only aluminum-doped zinc oxide is added, and in Comparative Example 5, only indium tin oxide is added. This shows that the combination of aluminum-doped zinc oxide and indium tin oxide has a synergistic effect, which is better than the effect of using either of them alone. At the same time, the mass ratio of the combination of the two affects the synergistic effect of aluminum-doped zinc oxide and indium tin oxide.
[0063] Compared with Example 1-2, the resistance of the film material prepared in Comparative Example 1-2 increases and the conductivity decreases. Comparative Example 1-2 changes the amount of composite conductive material added. The amount of composite conductive material added decreases, and the conductivity of the inner layer decreases. As the amount of composite conductive material added decreases, uneven distribution is likely to occur, which reduces the conductivity of the inner layer.
[0064] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A transparent conductive film material, characterized in that: It includes two outer layers and an inner layer, the outer layer includes the following raw materials in parts by weight: 50-65 parts of high-density polyethylene powder and 2.5-4.8 parts of a conductive enhancer; the conductive enhancer is iron-hybridized multi-walled carbon nanotubes, and the inner layer includes the following raw materials in parts by weight: polyester particles and a composite conductive material, the addition amount of the composite conductive material is 5-8wt% of the polyester particles, and the composite conductive material includes aluminum-doped zinc oxide and indium tin oxide.
2. A transparent conductive film material according to claim 1, characterized in that: In the composite conductive material, the mass ratio of aluminum-doped zinc oxide to indium tin oxide is (1.62-1.75):(1.21-1.34).
3. The transparent conductive film material according to claim 1, characterized in that: The preparation method of the iron-hybridized multi-walled carbon nanotubes comprises the following steps: ultrasonically dispersing the multi-walled carbon nanotubes, ferric chloride and ferrous sulfate heptahydrate in water, introducing nitrogen and mixing for 2 hours, dripping ammonia water, placing the mixed solution in an oven at 60° C. for 3 hours after the dripping is completed, precipitating, centrifuging and washing to obtain the iron-hybridized multi-walled carbon nanotubes.
4. The transparent conductive film material according to claim 3, characterized in that: The mass ratio of the ferric chloride, ferrous sulfate heptahydrate and multi-walled carbon nanotubes is (1.32-1.68):(0.67-0.73):(0.11-0.15).
5. The transparent conductive film material according to claim 1, characterized in that: The iron hybrid multi-walled carbon nanotubes are also subjected to a silicon dioxide coating treatment: the iron hybrid multi-walled carbon nanotubes are mixed with anhydrous ethanol and water, and after being uniformly dispersed by ultrasonication, an ethanol solution of tetraethyl orthosilicate is added dropwise, and the reaction is carried out for 24 hours after the addition is completed, an ethanol solution of a silane coupling agent is added dropwise, and the reaction is continued for 24 hours, and then the mixture is filtered, washed, and vacuum dried.
6. The transparent conductive film material according to claim 5, characterized in that: The iron hybrid multi-walled carbon nanotubes coated with silica are further treated as follows: ultrasonically dispersing the iron hybrid multi-walled carbon nanotubes coated with silica in a pyrrole hydrochloric acid solution, stirring in an ice-water bath for 30 minutes, adding ferric chloride solution dropwise, stirring at 0-5° C. for 2.5 hours, filtering and drying.
7. The transparent conductive film material according to claim 6, characterized in that: The mass ratio of the iron hybrid multi-walled carbon nanotubes after the silicon dioxide coating treatment to pyrrole is (1.68-1.75):(0.92-1.03).
8. The method for preparing the transparent conductive film material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing high-density polyethylene powder with a conductive enhancer to prepare an outer layer raw material for use; mixing polyester particles, aluminum-doped zinc oxide and indium tin oxide to prepare an inner layer raw material for use; and co-extruding the outer layer raw material and the inner layer raw material in an outer layer-inner layer-outer layer arrangement to prepare a transparent conductive film material.
Citation Information
Patent Citations
Method for preparing silicon dioxide-coated magnetic microspheres
CN101783217A
Flexible hybrid carbon wave-absorbing nanopaper and production method thereof
CN109180070A
Preparation method of environment-friendly multifunctional polyester film
CN109421288A
Permanent antistatic polyethylene (PE) microporous breathable film for medical protective clothing and preparation method thereof
CN117734274A
Transparent conductive film, and manufacturing method thereof
JP2009163959A